2012
DOI: 10.1063/1.4766390
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of silicon co-implanted with carbon and high energy proton for the formation of the lasing G-centre

Abstract: High dose rate effects in silicon by plasma source ion implantation J. Vac. Sci. Technol. B 17, 863 (1999) We investigate a new approach for efficient generation of the lasing G-centre (carbon substitutional-silicon self-interstitial complex) which crucially is fully compatible with standard silicon ultra-large-scale integration technology. Silicon wafers were implanted with carbon and irradiated with high energy protons to produce self-interstitials that are crucial in the formation of the G-centre. Rutherfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
8
0
1
Order By: Relevance
“…The pair is associated with a G-center which emits light at 0.97 eV (1280 nm). 1,2 It was discovered in the 60's as a by-product in the silicon crystal caused by the radiation damage due to bombardment with high-energy electrons, ions and gamma rays. In recent years, significant efforts have been deployed to increase the concentration of G-centers [1][2][3] , generally through surface alteration of silicon, followed by laser annealing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pair is associated with a G-center which emits light at 0.97 eV (1280 nm). 1,2 It was discovered in the 60's as a by-product in the silicon crystal caused by the radiation damage due to bombardment with high-energy electrons, ions and gamma rays. In recent years, significant efforts have been deployed to increase the concentration of G-centers [1][2][3] , generally through surface alteration of silicon, followed by laser annealing.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 It was discovered in the 60's as a by-product in the silicon crystal caused by the radiation damage due to bombardment with high-energy electrons, ions and gamma rays. In recent years, significant efforts have been deployed to increase the concentration of G-centers [1][2][3] , generally through surface alteration of silicon, followed by laser annealing. These technologies have promising applications in the development of a silicon laser.…”
Section: Introductionmentioning
confidence: 99%
“…It is also likely that the implant conditions for these centers must also be optimized. For example, electroluminescence of the G-center in silicon has been observed 11 , and G-centers have been fabricated via ion implantation of C followed by proton irradiation 37 . Meanwhile, studies on the depth dependence of the G center PL 27 have indicated that the G centers are formed at even larger depths relative to the projected range than the W center.…”
Section: Further Workmentioning
confidence: 99%
“…G中心通常以离子注入的方式 引入, 在1.28 μm(0.97 eV)处有尖锐的发光峰, 其发光 性能受碳浓度、结构和费米能级的影响 [41] . 2012年, Berhanuddin等人 [42] 通过离子注入碳和退火处理, 得到 含位错环的样品, 利用其增强发光效率和降低温度猝 灭的效应, 得到较高温度下G中心的高效发光.…”
Section: 硅量子点发光unclassified